2010
DOI: 10.1002/cctc.201000037
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Composition, Morphology and Reaction Pathway in the Growth of “Super‐Long” Carbon Nanotubes

Abstract: What took so long? An ex situ investigation of an iron–aluminum nanocatalyst that is active in the water‐assisted growth of “super‐long” carbon nanotubes (CNTs) with different techniques (HRSTEM, EELS, XPS, GIXRD) reveals for the first time its bimetallic nature. Besides metallic aluminum and iron, mixed oxides, hydroxides, and aluminum oxycarbides play a role in the CNT growth process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…The growth conditions (gas flow, heating and cooling rate, water flow, etc.) are described in [31][32][33]. TEM did not show deposition of amorphous carbon on the walls of the as-grown CNTs (Fig.…”
Section: Synthesis and Purity Of The Vacnt Arraysmentioning
confidence: 84%
“…The growth conditions (gas flow, heating and cooling rate, water flow, etc.) are described in [31][32][33]. TEM did not show deposition of amorphous carbon on the walls of the as-grown CNTs (Fig.…”
Section: Synthesis and Purity Of The Vacnt Arraysmentioning
confidence: 84%
“…15 Wellcontrolled amounts of water vapor were introduced into the system by blowing a small amount of gas through a water bubbler by means of a water sensor ͑Michell Instruments͒. Al and Fe react together to produce bimetallic catalyst nanoparticles, which then catalyze the CNT growth.…”
Section: A Growth Of Cnt Blocksmentioning
confidence: 99%
“…Insufficient hydrogen causes the oxidized catalyst Fe to be reduced incompletely, while excessive hydrogen converted the carbon production in the gas phase into the reagents, thus decreasing the overall driving force of the process [41]. Joshi et al [37,42,43] experimentally observed the role of water and hydrogen in terms of their influence on CNT growth, and point out that hydrogen controls the cracking of the carbon precursor ethylene, thereby controlling the purity as well as the number of walls of the CNTs grown. Schaber et al [44,45] investigated the tribological properties of densely-packed VACNTs and the morphology effect on the frictional coefficients.…”
Section: Introductionmentioning
confidence: 99%